PERANAN PEREMPUAN DALAM MASYARAKAT PERTANIAN DI KABUPATEN TEMANGGUNG (STUDI KASUS PEREMPUAN PETANI TEMBAKAU DI DESA TLAHAP KECAMATAN KLEDUNG) (Faculty of Social Science, Universitas Negeri Semarang, 2009)
This is a qualitative research in the context of role, time allocation, income contribution, and women tobacco farmer contribution on decision making. The data source are collected through observation and in-depth interview with 5 families, including women tobacco farmer, their husbands, and their children, to fnd the description about women role in public and domestic activities. The research questions are: (1) what are the roles of women tobacco farmer in Tlahap Village Kledung Subdistrict Temanggung Regency? (2) how they allocate their time between domestic and public activities? and (3) how is their contribution in increasing family income? The result of this research shows that the women tobacco farmers have high contribution in their family income, around Rp. 2.000.000,00 – Rp. 3.000.000,00 every harvest, twice a year. Besides their work as farmer, they have side job that increase their family social economics condition. Women tobacco farmer work in farm about 9 hours a day and 5 hours in home, compare with their husband that only work 9 hours in farm. This fact shows that women tobacco farmer activities are longer than their husband.Keywords: Women, farm society, tobacco farmer